2011
DOI: 10.5194/acpd-11-10799-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aerosol modelling in Europe with a focus on Switzerland during summer and winter episodes

Abstract: This paper describes aerosol modelling in Europe with a focus on Switzerland during summer and winter periods. We modelled PM<sub>2.5</sub> (particles smaller than 2.5 μm in aerodynamic diameter) for one summer and two winter periods in years 2006 and 2007 using the MM5/CAMx air quality model system. The detailed AMS (aerosol mass spectrometer) measurements at specific locations were used to evaluate the model results. In addition to the base case simulations, we carried out sensitivity tests with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Rather, increase in wind speed can induce increase in inhalational exposure to pollen, allergens and air pollutants (36), leading to bronchiolar spasms and air trapping inside the blebs or bullae with a check valve mechanism (3,6,33). Perturbations in wind speed, rather than wind speed itself, cause dispersion of aerosol and drive atmospheric instability (37)(38)(39); this may be why variations in wind speed were associated with PSP in the present study. The relationship between changes in wind speed and PSP remained significant when including PSP events in smokers, whereas it diminished among PSP in non-smokers.…”
Section: Discussionmentioning
confidence: 63%
“…Rather, increase in wind speed can induce increase in inhalational exposure to pollen, allergens and air pollutants (36), leading to bronchiolar spasms and air trapping inside the blebs or bullae with a check valve mechanism (3,6,33). Perturbations in wind speed, rather than wind speed itself, cause dispersion of aerosol and drive atmospheric instability (37)(38)(39); this may be why variations in wind speed were associated with PSP in the present study. The relationship between changes in wind speed and PSP remained significant when including PSP events in smokers, whereas it diminished among PSP in non-smokers.…”
Section: Discussionmentioning
confidence: 63%
“…As AMS-observed NR-PM 1 mass concentration is compared to the simulated PM 2.5 in the following, the models are expected to give an overestimation of aerosol mass concentration. The difference between PM 1 and PM 2.5 mass concentrations can be high (previous studies report PM 1 /PM 2.5 mass ratios between 55 and 75%) and can vary according to the meteorological conditions and the emission rates of chemical compounds (Aksoyoglu et al, 2011;Spindler et al, 2013). However, the proportions of the predominant chemical components in NR-PM 1 and simulated PM 2.5 are expected to be of the same order.…”
Section: 3mentioning
confidence: 92%
“…Several authors have also mentioned lateral boundary conditions for aerosols as a source of uncertainties. Aksoyoglu et al (2011) concluded that the CAMx model reproduced the relative composition of aerosols very well over Switzerland but underestimated the absolute concentration by 20%. validated the online-coupled WRF/CHEM model against ground-based measurements over Europe.…”
Section: Introductionmentioning
confidence: 99%